Microscopic and molecular detection of piroplasms among sheep in Upper Egypt - Dyab, Ahmed Kamal; Mohamed, Sara Abdel-Aal; Abdel-Aziz, Fatma Mohamed; Gareh, Ahmed; Osman, Fathy; Elgohary, Fatma A.; Hassan, Ehssan Ahmed; Alsowayeh, Noorah; Alzaylaee, Hind; Ahmed, Abd Al-Rahman S.; Bravo-Barriga, Daniel; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2024)
Abstract Introduction: Blood parasites pose a significant threat to livestock production in southern Egypt, yet there is a scarcity of information regarding their circulation and epidemiology in sheep in this region. This study aimed to investigate the seroprevalence of blood parasite infections in sheep in Assiut governorate, Upper Egypt. Methods: A total of 400 blood samples were collected from sheep of varying ages and genders. The preliminary screening for the presence of piroplasms, mainly Babesia and Theileria spp., via microscopic examination, followed by investigation of the potential risk factors linked with the exposure to infection. Moreover, molecular identification of both parasites on some of positive samples was performed using PCR targeting Babesia 18S rRNA and Theileria annulata Tams1 gene. Results: The microscopic examination revealed that among the examined sheep, there was an overall prevalence of blood parasites at 44% (176 out of 400), with Babesia spp. observed in 14% (56 out of 400) and Theileria spp. in 30% (120 out of 400). Furthermore, the infection rate was non-significantly higher in young animals (50%) compared to adults (38.5%) (P= 0.246). Male sheep exhibited a significantly higher vulnerability to both parasites’ infection (63.3%) compared to females (35.7%) (P=0.011). Interestingly, the prevalence of both blood parasites was significantly higher during the cold season (66.1%) compared to the hot season (15.9%) (P= <0.001). The molecular analysis identified the presence of Babesia ovis and Theileria annulata among a subsample of the positive sheep's bloods films. The identified species were recorded in the GenBank™ databases and assigned specific accession numbers (OQ360720 and OQ360719 for B. ovis), and (OP991838 for T. annulata). Conclusions: Taken together, this study confirms a high prevalence of piroplasmosis and offers epidemiological and molecular insights into blood parasites in sheep from Upper Egypt, highlighting the importance of detecting these parasites in various hosts and their competent vectors (ticks).